2022
DOI: 10.14321/aehm.025.04.37
|View full text |Cite
|
Sign up to set email alerts
|

Cage farming in the environmental mix of Lake Victoria: An analysis of its status, potential environmental and ecological effects, and a call for sustainability

Abstract: Lake Victoria is the second largest freshwater lake in the world that was once a biodiversity hotspot hosting over 500 endemic haplochromine cichlids that were later decimated by exotic introductions and anthropogenically driven environmental and ecological changes. The environmental and ecological changes in the lake over the years have been attributed to overfishing, eutrophication, introduction of exotic species, pollution and possibly climate change. The lake's capture fishery, which is the main economic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Nonetheless, changes in nutrient concentrations are shaped by both point and non-point sources of pollution [1,3,[6][7][8][9]. During spates, there is a lot of surface water run-off that carries much of the dissolved nutrients that are linked with sediments and also it is in such a season that leaching do occur from farmlands.…”
Section: Water Quality Parameters In Estuarine Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, changes in nutrient concentrations are shaped by both point and non-point sources of pollution [1,3,[6][7][8][9]. During spates, there is a lot of surface water run-off that carries much of the dissolved nutrients that are linked with sediments and also it is in such a season that leaching do occur from farmlands.…”
Section: Water Quality Parameters In Estuarine Ecosystemsmentioning
confidence: 99%
“…Globally, pollution of surface water is on the trajectory owing to rapid human population that is exerting enormous pressure on the environment. Anthropogenic activities have led to elevated physico-chemical water quality attributes of environmental concern because they have resulted into eutrophication and decreased biodiversity in aquatic ecosystems [1][2][3][4][5][6][7][8][9][10]. It has been confirmed that freshwater bodies although smallest in terms of surface area are the most important in sustaining human life and yet they are the most compromised in terms of integrity and their depletion is alarming [6][7][8][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, food production is an anthropogenic activity that has increased the use of fertilizers and available freshwater resources [2,3]. Freshwater scarcity is one of the most pressing global issues, affecting more than 40% of the world's population [4,5]. Furthermore, conventional food production systems are unable to meet the growing demand for the world's population due to arable land loss, water quality and quantity limitations, soil degradation, and nutrient depletion [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the low investment cost, convenience of installation and maintenance are also contributing to the expansion of cage activities (Gentry et al, 2017;Musinguzi et al, 2019). This is evident in Lake Victoria, where a rise in cage numbers from 1,663 to 4,537 between 2016 and 2019 and to 6,000 in 2021 is a glaring sign of sustained acceptance of cage aquaculture (Hamilton et al, 2020;Nyakeya et al, 2022). World inland aquaculture production as of 2021 was at 50% of the total fisheries production whereas in Africa, aquaculture contribution was at 18% with inland aquaculture constituting 92% of the total aquaculture production (FAO, 2022).…”
Section: Introductionmentioning
confidence: 99%